Kanatha, Syrien: Die Arbeiten der Jahre 2012 und 2013 - Freyberger, Klaus Stefan (e-Forschungsberichte des DAI, 2023)
The main importance of sanctuaries for the community of Kanatha can be seen in their various functions. As centres of the public life they fulfilled religious, social, trade, therapeutic and personal needs of the local community. Moreover, they had privileges such as tax exemption and the right of asylum. It appears that some of the sanctuaries were in charge of the water supply thus securing a vital resource gradually turning them into some of the most important buildings of the settlement.